Sea dumping in Australia : historical and contemporary aspects - Plunkett, Geoff (Dept. of Defence and Dept. of the Environment Heritage, 2003)
This report brings together a number of studies undertaken on all aspects of sea dumping in Australia and its Territories. These were previously available in a number of disparate sources and have been collated here for convenience. At the date of publication, sea dumping in Australian waters is managed by the Department of the Environment and Heritage, Canberra.